Influence of in-class and after-class mathematics practice on students' achievement in selected secondary schools in ibadan north local government of Oyo State, Nigeria (2014)
This study examined the influence of In-class and After- class mathematics practices on students' achievement in mathematics in senior secondary within Ibadan North Local Government of Oyo State, Nigeria. 120 students between the ages of 14-20 years were sampled for the study; 60 males and 60 females; 30 each from four schools with 10 from each arm-science, social sciences and arts- from each school. Descriptive survey type was adopted for this study. Three questionnaires forms were used; the Student Practice Perception Questionnaire (SPPQ), Teacher Practice Approach Questionnaire (TPAQ) and Mathematics Achievement Test (MAT). The data were analyzed using frequency count, percentage, t-test, one way analysis of variance and correlation statistics. The result shows that the two practice assessment approaches have a positive correlation with students’ achievement with In-class practice having higher index (5.8%). Also no practice approach has an advantage over the other in influencing students’ achievement in mathematics. Furthermore, teachers most preferred practice approach correlates positively with students' most preferred approach. Lastly opportunity to practice or engage in mathematics has positive influence on students' achievement. The study recommends a combined and flexible use of In-class and After class practice approach as an opportunity to learn which help to improve students' achievement.